Notes—On the Efficiency of a Direct Search Method to Locate Negative Cycles in a Network - Yen, Jin Y. (Management Science, 1972)
The purpose of this note is to examine the efficiency of Direct Search Method (DSM) in terms of its computational upper bound. Comparisons of the efficiencies of DSM and other efficient algorithms (in terms of their computational upper bounds) are also presented.